Pentingnya Tabayyun dan Manajemen Media Dakwah - Erwan Efendi; Zahrani Fadila; Saniah Salsabila; Azhari; Veni Aqilla Rizki (STAI Terpadu Yogyakarta, 2023)
This journal focuses on the tabayyun attitude which is still relevant as a solution to the problems of da'wah in the era of digitalization. The phenomenon that occurred was found to be due to the dullness of critical understanding in the millennial generation. This is due to exposure to negative issues or ineffectiveness of the implementation of da'wah bi al-Tadwin in the era of digitalization, namely related to digital da'wah videos on social media applications with a short duration of time and without clear sources of information. Thus, the actualization of tabayyun is a wise solution for digital da'wah scholarship through understanding the contextualization of hadith. This hadith narrated by Imam Ahmad bin Hanbal is one of the hadiths that discusses tabayyun. The hadith analyzes data problems and uses ma'anil hadith studies. The research object of the tabayyun hadith, describes three problem formulations, namely first, what is the quality and status of the authenticity of the tabayyun hadith in the history of Imam Ahmad bin Hanbal. Second, what is the meaning of the hadith narrated by Imam Ahmad bin Hanbal number for implementing short duration da'wah in the era of digitalization. Third, how to contextualize the tabayyun hadith as a wise attitude or Ahsan al-'Amal in overcoming the da'wah phenomenon in the era of digitalization. This conclusion includes the status of the hadith studied as having Sahih lizatihi quality so that it can be used as evidence. The actualization of tabayyun is a warning and demand for Muslims, because the values contained in this attitude are an example of Akhalq al-Karimah. Rasulullah SAW or Ahsan al-'Amal in receiving and conveying information. The contextualization of tabayyun in the era of digitalization adheres to two principles, namely the principle of selectivity or validity and the principle of Qaulan Sadida as confirmed by the verses of the Koran and the hadith of the Prophet. Qualitative methods, collect descriptive data to gain an indepth understanding of a phenomenon, often through interviews, observations, or text analysis.